DEMOCRACY AND DEMOCRATIZATION IN THE MUSLIM WORLD: AN EVALUATION OF SOME IMPORTANT WORKS ON DEMOCRATIZATION IN SOUTH/SOUTHEAST ASIA - Tauseef Ahmad Parray (Balai Penelitian dan Pengembangan Agama Semarang, 2017)
Is Islam compatible with democratization in the context of Asian cultures? To address this important issue, a series of books have been published in the English language from 1990s (and especially from 2000s). Most of these books deal with the relationship between Islam, Muslims, and democratization with a sub-region in Asia: South Asia, Southeast Asia, and Central Asia. While others deal with same issues with a focus on the future, very few deal with the relationship between Islam, Muslims, and democratization in the context of Asian cultures from the perspectives of theory and empirical country studies from all three Asian regions. In this backdrop, this essay—by making an assessment and review of the literature, produced in the last decade, on this theme—focuses on the compatibility paradigm in South and South East Asian Muslim societies at the empirical level, with a focus on Pakistan, Bangladesh, Malaysia, and Indonesia. To achieve this objective, the essay follows the analytical and comparative methodology, and evaluates these four important books: Zoya Hasan (2007); Shiping Hua (2009); Mirjam Künkler and Alfred Stepan (2013); and John Esposito, Tamara Sonn, and John Voll (2016). A due support is taken from other related works (books and journal articles) as well in substantiating, supporting, and strengthening the argument(s) put forth in this essay.